Development and initial hover testing of the Mach scaled rotor test rig MERIT - Heuschneider, V.; Berghammer, F.; Pflumm, T.; Hajek, M. (My University, 2021)
The first part of this paper shows the development of the rotor test rig MERIT, designed and built at the Institute of Helicopter Technology, Technical University of Munich, Germany. It includes insight into mechanical component design, such as the rotor head, rotor blade, blade attachment, and swashplate as well as the measurement and data acquisition system architecture in the rotating and stationary frames with regard to the most restrictive design target, which is dynamic stall investigation in forward flight conditions. Test results show that the critical components’ tensile strengths and eigenfrequencies meet the requirements. Furthermore, calibration results for the rotor load measuring cells are given. The second part focuses on hover tests, displaying the AREA rotor´s polar measurement results for power and thrust up to 12_ collective pitch and at 550 to 800rpm. A comparison of these whirl test results with free flight measurements show very good compliance with the power and thrust values of one AREA rotor in flettner configuration on the AREA drone.